Wielkość wskaźnika Rohrera w aspekcie wybranych czynników środowiskowo-społecznych = The size of Rohrer`s index in relation to selected environmental and social factors - Tatarczuk, Józef; Wandycz, Artur (Zielona Góra: Lubuskie Towarzystwo Naukowe)
The article aims to determine the size of Rohrer`s index in relation to age and environ-mental and social factors. The study was conducted in selected schools of the Lubuskie Voivodeship between 2015 and 2017. The age of the researched was between 7 and 18. Together, 11680 persons (6080 girls and 5600 boys) were involved. Among somatic features, height and body mass were measured with the Martin technique as described by Ćwirko-Godycki and Drozdowski. Rohrer`s index was calculated on the basis of these features. The information on social variables was gathered by means of a questionnaire. The questions concerned age, living environment, and parents` education.`
Keywords: wskaźnik Rohrera; modyfikatory rozwoju; dziecko; młodzież; Rohrer`s index; development modifiers; child; youth